A taxonomy for modelling and analysis of diffusion of (mis)information in social networks. (1st January 2014) - Kumar, Krishna K.P.; Geethakumari, G.
The use of internet as a medium for communication, e-commerce, education and entertainment has grown many-fold in the last decade. There is an ever increasing dependence on such networks to obtain information. In this scenario, social networks have come to play a very decisive role in the transmission of information and as a medium for exerting influence in the population. The role played by different social networks in keeping the netizens updated has proved to be very efficient. However, the implicit faith in the transmission of information through this media has become counterproductive many times in the recent years. Their use in the manipulation of information and the resulting spread of misinformation has far reaching consequences in influencing the behaviour of the population. The aim of this paper is to review the models of diffusion of information in the social networks with specific stress on misinformation and the factors governing its spread in terms of time and size.